Atitudes colaborativas interprofissionais na estratégia saúde da família da região metropolitana de São Luís, Maranhão - GRAÇA, Ilana Barros Moraes da (2022)
Collaborative attitudes promote an integrated, shared interprofessional approach in order to provide care centered on the user, family and community. Thus, the objective of the study was to identify collaborative attitudes and their associated factors in professionals of the Family Health Strategy (ESF) in the Metropolitan Region of São Luís (Maranhão). This is a cross-sectional, analytical study with 311 higher education professionals who work in the FHS. Data collection took place through an electronic form, which addressed questions regarding sociodemographic characteristics, professional training, the work process and collaborative attitudes based on the Jefferson Scale of Attitudes Related to Interprofessional Collaboration (EJARCI). For the analysis of the EJARCI, the sum of all 20 responses was performed, categorizing them into tertiles. The internal consistency of the EJARCI questionnaire responses was evaluated by Cronbach's Alpha, with a value of =0.806. To verify the association between the responses of the Jefferson scale and the other variables, bivariate analyzes were performed using Pearson's Chi-Square test at a significance level of 5% (p< 0.05). All analyzes were performed using Stata software, version 14. Most professionals were female (79.74%), brown (50.8%), residing in São Luís (77.17%), aged between 30 and 39 years old (36.01%), with training in nursing (53.38%) and with specialization in Family Health/Public Health/Collective Health (44.05%). The average EJARCI score among professionals was 128 (95%CI 119-134) for medicine, 126.5 (95%CI 118.75-132) for nursing and 124 (117-134) for dentists, without statistical significance. The variables type of specialization (p=0.008) and time working in the FHS (p=0.02) were associated with collaborative attitudes. The results of this study show collaborative attitudes among ESF professionals in the metropolitan region of São Luís/MA, and the type of specialization and working time in the ESF were associated with more collaborative attitudes, which contributes to the deconstruction of the hierarchical model of health care.